THE ROLE OF INFORMATION COMMUNICATIONS IN THE DEVELOPMENT OF TOURISM - Shodiyeva, Guzal (YANGI O‘ZBEKISTONDA MILLIY TURIZM ISTIQBOLLARI, 2024)
This article explores the pivotal role of Information and Communication Technologies in the development and growth of the tourism industry. It highlights how Information and Communication Technologies has revolutionized marketing, customer service, and operational efficiency within the tourism sector. The integration of digital tools and platforms has enhanced the accessibility and appeal of tourism services, leading to increased global reach and customer satisfaction. The article also discusses the future prospects of Information and Communication Technologies in tourism and the potential challenges that need to be addressed.